Trust Me. - Dickenson, Jackie (University of New South Wales Press, 2013)
A lively look at the deep distrust between Australians and the people they elect to office, this book showcases the long history of such an uneasy relationship. From the 1850s to the 2013 election, Jackie Dickenson traces the ways in which such animosity has, and hasn't, changed over the course of time. While acknowledging the maxim that cynicism about politics is always on the rise, she argues that having blind trust in the government is not a desirable alternative either. Asking tough questions, revisiting scandals, and exploring times of trau.